Stem cell therapy for urethra and ureter tissue engineering: A systematic literature review on animal studies - Hamoon Baghaei; Ali Faegh; Shima Jahani; Pooya Hekmati; Masoumeh Majidi Zolbin (Regenerative Therapy)
The present study investigates the optimal stem cells for using in ureter and urethra tissue engineering by systematically reviewing the literature. Scopus, PubMed, and Embase databases were searched up to December 2024 to find original studies investigating ureter and urethra tissue engineering by seeding stem cells on the scaffolds in animal models, which resulted in the identification of 1191 studies. Finally, 26 studies were included. Eighteen and eight studies tried urethra and ureter tissue regeneration, respectively. Adipose-derived stem cells were the most commonly used for tissue engineering of the ureter and urethra, with 14 studies. Bone marrow-derived stem cells were involved in 5 studies, urine-derived in 3, muscle-derived stem/precursor cells in 3, and human amniotic membrane-derived mesenchymal stem cells in 1. Bladder acellular matrix, artery extracellular matrix, and small intestinal submucosa were non-synthetic seeded scaffolds that were used in 10 studies. However, studies used biomaterial and synthetic scaffolds, including Poly (l-lactide-co-caprolactone) nano yarn, Poly-glycolic acid, nanofiber, double-modified sulfated bacterial cellulose, and silk scaffold more frequently. Data demonstrated that adipose-derived, bone marrow-derived, urine-derived, and human amniotic membrane-derived stem cells have the capability of both urothelium and smooth muscle regeneration in urethra reconstruction. Furthermore, seeding bone marrow-derived stem cells can improve collagen and vessel formation. Also, this study showed that the muscle-derived SCs or precursor cells are able to regenerate urethra smooth muscle, but data are limited. Hypoxia precondition, subcutaneous or omental pre-incubation, fibroblast growth factor receptor Ⅱ overexpression, and mechanical extension stimulation were employed as boosting conditions. However, data about ureter tissue engineering are limited. Adipose-derived stem cells were the most frequently employed for ureter tissue regeneration, with appropriate outcomes for both urothelium and smooth muscle regeneration however, other types of stem cells should be more investigated for ureter tissue engineering.